2020
DOI: 10.1177/0300060520974463
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and differential diagnosis of gastrofibromatosis-like undifferentiated carcinoma

Abstract: Objective To study the clinicopathological features and differential diagnosis of gastrofibromatosis-like undifferentiated carcinoma (GFLUC). Methods Three patients with GFLUC underwent histological and immunophenotypic analyses and fluorescence in situ hybridization to detect human epidermal growth factor receptor ( HER2) gene amplification. Results Among the three patients (2 male [36 and 44 years old], 1 female [58 years old]), two had lesions in the gastric body and one had lesions in the gastric antrum. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In addition, only major components and minor components are distinguished, and the histological types of various mixed components are not included (8). A previous study found that lymph node metastasis can still occur in the minor part of a gastric tumor of < 10% and the metastasis is the histomorphological change of < 10% (9). A pathological examination report-especially the one including any poorly differentiated tumors-is more conducive to the study of the characteristics, metastasis of recurrent tumors and the accurate treatment of primary mixed gastric tumors, which should be used for accurate treatment (10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, only major components and minor components are distinguished, and the histological types of various mixed components are not included (8). A previous study found that lymph node metastasis can still occur in the minor part of a gastric tumor of < 10% and the metastasis is the histomorphological change of < 10% (9). A pathological examination report-especially the one including any poorly differentiated tumors-is more conducive to the study of the characteristics, metastasis of recurrent tumors and the accurate treatment of primary mixed gastric tumors, which should be used for accurate treatment (10).…”
Section: Introductionmentioning
confidence: 99%